Predictors of outcome of mammography in the National Health Service Breast Screening Programme. - Banks, E; Reeves, G; Beral, V; Bull, D; Crossley, B; Simmonds, M; Hilton, E; Bailey, S; Barrett, N; Briers, P; English, R; Jackson, A; et al. (2002)
BACKGROUND: Little is known about the factors influencing the risk of recall for assessment, invasive diagnostic procedures, and early rescreening after screening mammography. METHODS: From June 1996 to March 1998 women attending screening at 10 National Health Service Breast Screening Programme (NHSBSP) centres completed a self administered questionnaire and were followed up for their screening outcome. RESULTS: 1969 (3.3%) out of 60 443 women aged 50-64 who had never used hormone replacement therapy (HRT) were recalled for assessment but were not diagnosed with breast cancer (defined here as false positive recall). After adjustment for the variation between centres, false positive recall was decreased significantly among women who were likely to have had a previous NHSBSP mammogram (odds ratio (OR) 0.49, 95% confidence interval (95% CI) 0.38 to 0.63 for likely versus unlikely), who were postmenopausal (OR 0.65, 95% CI 0.56 to 0.76 for postmenopausal v premenopausal) and increased significantly for women reporting previous breast surgery (OR 1.64, 95% CI 1.42 to 1.89). Although false positive recall decreased significantly with parity and increasing body mass index, these effects were not large and no significant variation was found with age, education, family history of breast cancer, oral contraceptive use, sterilisation, exercise, smoking, or alcohol consumption. Altogether 655 (1.1%) women had an invasive diagnostic procedure; no personal characteristics were predictive of this outcome, 286(0.5%) were referred for early rescreening, and this was increased significantly by nulliparity and a family history of breast cancer. INTERPRETATION: Premenopausal women, those without a previous NHSBSP mammogram, and women with previous breast surgery have an increased risk of false positive recall by the NHSBSP.